2014
DOI: 10.1016/j.socscimed.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

No time for the gym? Housework and other non-labor market time use patterns are associated with meeting physical activity recommendations among adults in full-time, sedentary jobs

Abstract: Physical activity and inactivity have distinct cardio-metabolic consequences, suggesting that combinations of activities can impact health above and beyond the effects of a single activity. However, little work has examined patterns of non-labor market time activity in the US population, particularly among full-time employees in sedentary occupations, who are at increased risk of adverse health consequences associated with a sedentary lifestyle. Identification of these patterns, and how they are related to tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 65 publications
5
31
0
1
Order By: Relevance
“…29 It was reported that low-income employees face signifi cant work-related (long hours) and fi nancial barriers to achieving physical activity goals. 30 Our results were consistent with those of previous reports. In addition, we reported that participants with a higher household income level had a signifi cantly better performance on the 50-metre dash run (speed), sit-ups (muscular endurance) and grip strength (muscular strength) than the performance of those with lower household income levels.…”
Section: Discussionsupporting
confidence: 94%
“…29 It was reported that low-income employees face signifi cant work-related (long hours) and fi nancial barriers to achieving physical activity goals. 30 Our results were consistent with those of previous reports. In addition, we reported that participants with a higher household income level had a signifi cantly better performance on the 50-metre dash run (speed), sit-ups (muscular endurance) and grip strength (muscular strength) than the performance of those with lower household income levels.…”
Section: Discussionsupporting
confidence: 94%
“…If the more complex cluster solution generated meaningful subgroups, the more complex cluster solution was chosen, as long as the pseudo F-statistic value was comparable. 20 …”
Section: Methodsmentioning
confidence: 99%
“…This could be confirmed by the identification of a lack of time as one of the main barriers to leisure-time physical activity. 13 It is also necessary to determine whether the sedentary behavior adopted on the weekend, a period characterized by longer leisure-time for most of the adult population, is also associated with other behaviors. Furthermore, strategies designed to reduce this behavior, specifically during this period, could have health benefits and are more easily implemented by workers with high workloads, considering that the works' health entails significant public expenditures in developing countries.…”
Section: Introductionmentioning
confidence: 99%